(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the post-tonsillectomy nausea and vomiting with and without a single intra-operative intravenous dose of dexamethasone 0.5mg/kg. Study Design: Randomized controlled trial Place and Duration of Study: This study was conducted at the Department of ENT, Sir Ganga Ram Hospital Lahore from August 2018 to August 2019. Materials and Methods: One hundred and forty patients were equally divided into two groups. Group I was treated with dexamethasone 0.5mg/kg and Group II was treated without dexamethasone. Complete laboratory examination was done. Tonsillectomy was performed by sharp dissection snare technique in all the patients by the same surgeon. Post-operatively 8-hourly Amoxicillin/clavulanic acid 15mg/kg orally, paracetamol 15 mg/kg and povidone iodine mouth wash were given to all the patients. Results: The mean age in Group I was 12.37±5.84 and in Group II it was 10.82±4.37 year. There were 34 (48.6%) males in group I and 36 (51.4%) males in group II, while females were 36 (51.4%) in group I and 34 (48.6%) in group II. Postoperative nausea and vomiting was observed in 5 patients (7.1%) of group I and 19 patients (27.1%) of group II (p=0.002). Mean duration of disease was 3.87±1.21 and 2.96±0.98 year in group I and II, respectively (Table-4). Mean BMI in group I was 17.96±2.68 and in group II 17.47±0.98 (kg/m2). Conclusion: Single intravenous dose of dexamethasone 0.5mg/kg intra-operatively is safe and effective for the prevention of post-operative complications such as nausea and vomiting in patients undergoing tonsillectomy.